CREDIT RISK MANAGEMENT AND PROFITABILITY OF DEPOSIT MONEY BANKS IN NIGERIA - Alade Ayodeji ADEMOKOYA; Mubarak Olajide SALAMI; Halimat Bukola ISAU; Habeeb Abiola IBRAHIM (Malete Journal of Accounting and Finance)
Banks in all climes are primarily faced with problem of credit risk whenever they mediate between the surplus and the deficit units of the economy. This study examined the impact of credit risk management on the profitability of deposit money banks in Nigeria. Specifically, this study evaluated the impact of credit risk management on return on assets, return on equity, and net operating income of deposit money banks in Nigeria. This study adopted an ex post facto research design. Nineteen listed deposit money banks as at December 31, 2018 form the population of this study out of which a sample of fifteen banks were selected based on complete availability of data from 2007-2018. Data obtained was subjected to fixed and random effects regression estimations for the various models in this study using the Hausman test. Findings revealed that: (i) loan-value ratio and loan-deposit ratio significantly impacted on return on assets of deposit money banks, while non-performing loan ratio, bank size, and log of total loans did not significantly impact on return on assets of deposit money banks in Nigeria; (ii) total loans significantly affected return on equity of deposit money banks, while loan-value ratio, loan-deposit ratio, bank size, and non-performing loans did not significantly affect return on equity of deposit money banks in Nigeria; and (iii) bank size, non-performing loan, and total loans were found to significantly affect net operating income of deposit money banks in Nigeria, while loan-value ratio, and loan-deposit ratio did not significantly exert on net operating income of deposit money banks in Nigeria. The study therefore, concluded that loan-value ratio, loan-deposit ratio, value of total loans, bank size, and non-performing loans influence banks profitability in Nigeria, and recommended that proper attention be paid to these variables in order to increase the profitability of deposit money banks in Nigeria.